Analysis Results and Impact of the Sekolah Penggerak Program at Kolese Xaverius Ambon High School - Rahabav, Patrisius; Makaruku, Vando Kristi (KnE Social Sciences, 2024)
This study describes the results and impact of the Sekolah Penggerak program at Kolese Xaverius Ambon High School. The focus of the research is four dimensions, including: Sekolah Penggerak program preparation, Sekolah Penggerak program planning, Sekolah Penggerak program implementation as well as results and Sekolah Penggerak program impacts. This research uses a descriptive-analytical approach used to describe in depth research problems to describe descriptively the phenomena that occur in the field. The participants this research were the school principal and deputy head of curriculum. The data collection techniques used were assessment rubrics, observation, free interviews and documentation studies. Data analysis was carried out descriptively (quantitative and qualitative). The results of data analysis in all dimensions obtained the results: 100%+92%+72%+87.5=351.5%/4= 88%. These results are in the category: (75% < The results of the analysis of dimension 1: Driving School Preparation obtained 100% results. These results are in the category (75% < X ≤ 100% = 4) meaning very good. Results of data analysis on dimension 2: Sekolah Penggerak program Arrangement, obtained a result of 92%. These results are in the category (75% < X ≤ 100% = 4) meaning very good. Results of analysis of dimension 3: Sekolah Penggerak program implementation the drive obtained a yield of 72%. These results are in the category (50% < X ≤ 75% = 3) which means good. Results of data analysis on dimension 4: Sekolah Penggerak program results and impact a result of 87.5% was obtained. These results are in the category (75% < X ≤ 100% = 4) meaning very good. The results obtained include: the school principal has become a role model by implementing team leadership, understanding assessment, learning tools, innovative learning models and information technology this has implemented differentiated learning, both content, process and product differentiation. There has been an increase in literacy, numeracy, character and school reports. Perceived impact: Energy used for partner schools, one student Kolese Xavier Ambon High School passing the selection and getting a scholarship to study in the United States, enthusiasm for entering high school, the trend of students graduating and entering their favorite college. Keywords: analysis, Sekolah Penggerak Program, leadership, assessment, school principal